No change in type 2 diabetes prevalence in children and adolescents over 10 years: Update of a population‐based survey in South Germany. Issue 4 (12th December 2017) - Neu, A; Feldhahn, L; Ehehalt, S; Ziegler, J; Rothe, U; Rosenbauer, J; Holl, RW
Abstract : Objective of this study was to analyze prevalence changes in type 2 diabetes (T2D) among children and adolescents over the last 10 years. We performed a cross‐sectional survey in Baden‐Württemberg (BW), Germany, by using a written questionnaire and comparing these results with T2D prevalence data from the same area retrieved in 2004/2005. In 2016, 50 patients with T2D under 20 years of age were registered in BW, Germany, which corresponds to a prevalence rate of 2.42 per 100 000 (95% confidence interval [CI]: 1.75‐3.09). The prevalence rate found in the same geographic area 10 years prior was 2.30 per 100 000 (95% CI: 1.70‐2.90). Overall, 70% of T2D patients of this age group were treated by adult diabetologists. Concisely the prevalence of T2D in children and adolescents is still low in South Germany, remaining practically unchanged over the past decade.